Agency in ancient China. Issue 4 (4th July 2022) - Zhao, Yukun; Seligman, Martin; Peng, Kaiping; Ye, Leyang; Liang, Cheng; Wang, Huicong; Gao, Haibo
ABSTRACT: Seligman (2020) hypothesized that individuals' beliefs in Agency proximally cause progress and innovation. When agency is high, progress occurs, when low, stagnation. This seems to be true in the Greco-Roman epoch and we examined this in ancient China. The Shang (1600– 1046 BCE) devoutly followed the arbitrary will of gods and there was little progress. The Zhou (1045– 256 BCE) believed more in human agency and this was a time of progress. In the Axial Age (530 BCE－221 BCE), Confucianism emphasized human agency and progress was remarkable. In the first Imperial Age (221 BCE – 220 CE), when Legalism dominated, there was massive collective progress, followed by chaos. Eventually a hybrid of Legalism-Confucianism became the dominant ideology. Collective agency and individual agency were well-balanced, and there was considerable progress. We confirmed Seligman's claim for Ancient China, but with the major addition of collective agency.